Voluntary action for climate change mitigation does not exhibit locational preferences - Diederich, Johannes; Goeschl, Timo (Journal of environmental economics and management, 2018)
The climate system is indifferent as to the location of voluntary mitigation activities. Are people? Our artifactual online field experiment varies, for residents of a European Union member state, (1) whether the location of a real CO2 mitigation measure is made salient or not or (2) whether the salient location is in the European Union or in a developing country. Harnessing between- and within-subjects variation in our panel data and controlling for cost effectiveness, we find that subjects respond to the location being made salient. Contrary to previous evidence, however, they are indifferent between mitigation sites. We conclude that locational preferences need not stand in the way of realizing the gains from comparative advantage in climate change mitigation.
Available online 28 March 2018
Gesehen am 17.04.2019